The family in Shakespeare's plays: a study of South African revisions - Hjul, Lauren Martha (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2013)
This thesis provides a detailed consideration of the family in Shakespeare's canon and the engagement therewith in three South African novels: Hill of Fools (1976) by R. L. Peteni, My Son's Story (1990) by Nadine Gordimer, and Disgrace (1999) by J. M. Coetzee. The study is divided into an introduction, three chapters each addressing one of the South African novels and its relationship with a Shakespeare text or texts, and a conclusion. The introductory chapter provides an analysis of the two strands of criticism in which the thesis is situated "“ studies of the family in Shakespeare and studies of appropriations of Shakespeare "“ and discusses the ways in which these two strands may be combined through a detailed discussion of the presence of power dynamics in the relationship between parent and child in all of the texts considered. The three chapters each contextualise the South African text and provide detailed discussions of the family dynamics within the relevant texts, with particular reference to questions of authority and autonomy. The focus in each chapter is determined by the nature of the intertextual relationship between the South African novel and the Shakespearean text being discussed. Thus, the first chapter, "The Dissolution of Familial Structures in Hill of Fools" considers power dynamics in the family as an inherent part of the Romeo and Juliet genre, of which William Shakespeare's Romeo and Juliet is but a part. Similarly, the impact of a socio-political identity, and the secrecy it necessitates, is the focus of the second chapter, "Fathers, Sons and Legacy in My Son's Story" as is the role of Shakespeare and literature within South Africa. These concerns are connected to the novel's use of Shakespeare's Sonnets, King Lear, and Hamlet. In the third chapter, "Reclaiming Agency through the Daughter in Disgrace and The Tempest" , I expand on Laurence Wright's argument that Disgrace is an engagement with The Tempest and consider ways in which the altered power dynamic between father and daughter results in the reconciliation of the father figure with society. The thesis thus addresses the tension between parental bonds and parental bondage
Keywords: Parents; Parental bonds; Family; Shakespeare, William, 1564-1616 -- In literature -- Research; Coetzee, J M, 1940-. Disgrace; Gordimer, Nadine. My son's story; Peteni, R L, 1915-. Hill of fools; English drama -- 17th century -- History and criticism; Families in literature; English literature -- History and criticism